Social memory and its literary forms in Greek epic and tragedy - Schade, Gerson (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2012)
Several Homeric departure-scenes, depicting a son leaving his father, contain as their central theme the idea of becoming such a hero as one’s father was. In light of the new concept ‘social memory’ it is no wonder that the central message of the heroic code, ‘always try to excel’, is part of the conversation during the departurescenes, for the simple reason that this phrase and those connected with it define the social memory of the heroic society, the ‘heroic code’. Reminiscences of one’s father and his words mean much to heroes, structure their lives, provide a frame, and help them to cope with the current situation.
Keywords: Social memory; heroic code; departure-scene; ‘always try to excel’